CHARACTER OF NATASHA ROSTOVA IN THE NOVEL “WAR AND PEACE” BY LEO TOLSTOY - Saidaposhsho Azizova; N. Mukhammedova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article provides information about the novel “War and Peace” written by Leo Tolstoy by analysing novel and deeply goes through the character of Natasha Rostova.